DIFFERENCE OF BREAST CANCER ESTROGEN RECEPTOR (ER) BETWEEN OBESE PRE-MENOPAUSE WOMEN AND OBESE POST-MENOPAUSE WOMEN - Viqi Vincentius Julio; Sindrawati Sindrawati; Fransiscus Arifin (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: One of the risk of breast cancer is Obesity (BMI > 23Kg/m2) related to estrogen production between pre-menopause and post-menopause.Aim: To investigate the difference of breast cancer estrogen receptor (ER) in obese women based on menopausal status.Methods: This study was retrospective cross-sectional from secondary data (Medical Records) from Poliklinik Onkologi Satu Atap (POSA) RSUD Dr. Soetomo (ICD-10 C50) from 2013-2017 with inclusion criteria was BMI >23Kg/m2. Data were analyzed using Chi-Square. Â Results: There were 138 patient medical records collected which is 63 were obese pre-menopause and 75 were obese post-menopause. There were statistically a significant difference (p<0,05) based on Chi square test of breast cancer estrogen receptor for obese post-menopause women (66,7%) to obese pre-menopause (39,7%). Obese post-menopause women have 1,68 times greater risk factor to become estrogen receptor positive (ER+) compared to obese pre-menopause women. (PR = 1,68; 95% CI = 1,191-2,370) Â Conclusion : There is a significant difference of breast cancer estrogen receptor in obese post-menopause women more frequent than obese pre-menopause women.